Electrocatalytic properties of diiron ethanedithiolate complexes containing benzoate ester. (6th September 2018) - Chen, Fei‐Yan; He, Jiao; Yu, Xiao‐Yong; Wang, Zheng; Mu, Chao; Liu, Xu‐Feng; Li, Yu‐Long; Jiang, Zhong‐Qing; Wu, Hong‐Ke
Abstract : Six diiron ethanedithiolate complexes containing benzoate ester have been synthesized and characterized. Treatment of the starting material [{μ‐SCH2 CH(CH2 OH)S}Fe2 (CO)6 ] (1 ) with benzoic acid in the presence of N, N ′‐dicyclohexylcarbodiimide and 4‐dimethylaminopyridine afforded the benzoate ester‐containing complex [{μ‐SCH2 CH(CH2 O2 CPh)S}Fe2 (CO)6 ] (2 ) in 97% yield. Carbonyl substitution of complex2 with a monophosphine ligand, such as triphenylphosphine, tris(2‐methoxyphenyl)phosphine, tris(4‐fluorophenyl)phosphine, isopropyldiphenylphosphine or cyclohexyldiphenylphosphine, in the presence of Me3 NO⋅2H2 O gave the derivatives [{μ‐SCH2 CH(CH2 O2 CPh)S}Fe2 (CO)5 L] (L = PPh3, 3 ; P(C6 H4 OCH3 ‐2)3, 4 ; P(C6 H4 F‐4)3, 5 ; Ph2 PCH(CH3 )2, 6 ; Ph2 PC6 H11, 7 ) in 66–95% yields. Complexes2 –7 were characterized using elemental analysis, spectroscopy and X‐ray diffraction analysis. In addition, these complexes can catalyze the reduction of protons to H2 in the presence of weak acid HOAc under electrochemical conditions. Abstract : Six diiron complexes were prepared by esterification or carbonyl substitution and structurally characterized using elemental analysis, infrared and NMR spectroscopies and X‐ray crystallography. In addition, the electrochemical properties of the complexes were studied using cyclic voltammetry.